Islamic Law and Local Traditions in Preventing Early Marriage in the Toraja Muslim Minority Community - Takdir, Takdir; Halide, Nirwana; Hardianto, Hardianto; Rusli, Muhammad; Erwin, Erwin; de Vos, Pierre (Jurnal Ilmiah Al-Syir'ah, 2024)
The enforcement of women's rights concerning the restriction of polygamy during the iddah period following divorce poses a significant challenge in Islamic family law, particularly among minority Muslim communities such as Tana Toraja. This issue reflects a broader tension between the principles of Islamic law and the influence of local cultural practices. Despite existing legal frameworks aimed at safeguarding women's rights, there remains a critical research gap in understanding how these frameworks operate in culturally distinct minority contexts. This study employs a comprehensive legal methodology, combining qualitative interviews with stakeholders from the local Religious Affairs Office, including religious leaders and legal practitioners, alongside document analysis of legal rulings, policies, and relevant literature. The findings reveal that local cultural norms often conflict with Islamic legal principles, exacerbated by limited legal awareness within the community and insufficient institutional enforcement mechanisms. These impediments hinder the effective application of Islamic family law and the protection of women's rights. To address these challenges, this study proposes two key strategies: (1) enhancing legal education programs tailored to the unique cultural contexts of minority Muslim communities and (2) strengthening oversight and enforcement mechanisms through collaboration among local authorities, religious leaders, and community organizations. By bridging the gap between Islamic legal principles and local cultural practices, these recommendations aim to promote a more inclusive and effective enforcement of women's rights within minority Muslim settings.